First, antiderivative = a solution to the indefinite integral
therefore to integrate -(csc(x))(cot(x)) first convert it to -cos(x)/sin2(x)
To integrate ∫-cos(x)/sin2(x) dx, use substitution u = sin(x) and du/dx = cosx
This will make it ∫-1/u2 du and the antiderivative is 1/u +c, therefore the answer is 1/sin(x) + c.
Chat with our AI personalities
Antiderivative of x/-1 = -1(x^2)/2 + C = (-1/2)(x^2) + C Wolfram says antiderivative of x^-1 is log(x) + C
d/dx (-cscx-sinx)=cscxcotx-cosx
It is -exp (-x) + C.
The antiderivative, or indefinite integral, of ex, is ex + C.
The antiderivative of x2 + x is 1/3x3 + 1/2x2 + C.